Conceptualization of theoretical and methodological paradigm of the building terms reserve calculation within the framework of implementation bases of optimization for the building processes organization of contracting companies - Radkevich А.; Arutiunian І.; Saikov, D. (Ways to Improve Construction Efficiency, 2019)
Dynamic evolution of the building services market in Ukraine dictates the emergence of modern trends in modeling of innovative approaches for the building processes organization system of contracting companies. Modernization of organizational bases for building production opens up the possibility of a fundamentally new regulation for erection terms of buildings with an endurance of a high-level quality of building works and objects in general. There is relevant the theoretical, methodological and practical solution to problems of organizational processes optimizationon basis of controlling the building end terms within the framework of regulatory obligations according to contract agreements. It has been researched the role and structure of the building production organization system of contracting companies in context of dynamic transformations in building market; determined the causes of appearance and influence of external factors on structural elements of the above-mentioned system. It has been also analysed the concept of building terms reserve, proposed the modernization of theoretical and methodological bases for term reserve calculating to ensure the effective functioning of the building processes organization system and controlling of building terms.